Protective effect of club cell secretory protein (CC-16) on COPD risk and progression: a Mendelian randomisation study. Issue 11 (24th August 2020) - Milne, Stephen; Li, Xuan; Hernandez Cordero, Ana I; Yang, Chen Xi; Cho, Michael H; Beaty, Terri H; Ruczinski, Ingo; Hansel, Nadia N; Bossé, Yohan; Brandsma, Corry-Anke; Sin, Don D; Obeidat, Maen
Abstract : Background: The anti-inflammatory pneumoprotein club cell secretory protein-16 (CC-16) is associated with the clinical expression of chronic obstructive pulmonary disease (COPD). We aimed to determine if there is a causal effect of serum CC-16 level on the risk of having COPD and/or its progression using Mendelian randomisation (MR) analysis. Methods: We performed a genome-wide association meta-analysis for serum CC-16 in two COPD cohorts (Lung Health Study (LHS), n=3850 and ECLIPSE, n=1702). We then used the CC-16-associated single-nucleotide polymorphisms (SNPs) as instrumental variables in MR analysis to identify a causal effect of serum CC-16 on 'COPD risk' (ie, case status in the International COPD Genetics Consortium/UK-Biobank dataset; n=35 735 COPD cases, n=222 076 controls) and 'COPD progression' (ie, annual change in forced expiratory volume in 1 s in LHS and ECLIPSE). We also determined the associations between SNPs associated with CC-16 and gene expression using n=1111 lung tissue samples from the Lung Expression Quantitative Trait Locus Study. Results: We identified seven SNPs independently associated (p<5×10 –8 ) with serum CC-16 levels; six of these were novel. MR analysis suggested a protective causal effect of increased serum CC-16 on COPD risk (MR estimate (SE) −0.11 (0.04), p=0.008) and progression (LHS only, MR estimate (SE) 7.40 (3.28), p=0.02). Five of the SNPs were also associated with gene expression in lung tissue (at false discovery rate <0.1) of several genes, including the CC-16-encoding gene SCGB1A1 . Conclusion: We have identified several novel genetic variants associated with serum CC-16 level in COPD cohorts. These genetic associations suggest a potential causal effect of serum CC-16 on the risk of having COPD and its progression, the biological basis of which warrants further investigation.